The inﬂuence of local, landscape and spatial factors on the distribution of the Lusitanian and the Mediterranean pine voles in a Mediterranean landscape - Santos, Sara M. (2012)
This study evaluated the relative contributions of local and landscape factors, and of spatial structure on the regional distribution of both the Lusitanian (Microtus lusitanicus Gerbe, 1879) and Mediterranean pine voles (Microtus duodecimcostatus de Selys-Longchamps, 1839) over an area of 1613 km 2 within a Mediterranean landscape in central Portugal. Three sets of explanatory variables (20 local, 23 landscape, and 6 spatial) were analysed independently by means of a generalized linear model, followed by a variance partitioning procedure. Variance in the distribution patterns of M. lusitanicus and M. duodecimcostatus largely was explained by ﬁne-scale environmental factors but spatial effects also were important, especially for the distribution of M. duodecimcostatus. The close proximity of verges and the high abundance of humidity and coarse sand in the soil were the most inﬂuencing local-scale factors for the presence of M. lusitanicus; meanwhile on a larger scale, the high abundance of linear habitats was the main landscape feature determining its occurrence. Regarding the presence of M. duodecimcostatus, the close proximity of verges, high tree canopy cover and herbaceous vegetation biomass were the most inﬂuential local explanatory variables for its occurrence, while the absence of shrubs in the surrounding habitat was the main factor regulating species presence at a landscape scale. Similarities identiﬁed between the two species primarily were related to descriptors of cover, food and burrows, while differences were related to opposing spatial trends and coarse-scale descriptors.